2012
DOI: 10.1590/s1516-05722012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de óleos essenciais de alfavaca (Ocimum gratissimum L.), orégano (Origanum vulgare L.) e tomilho (Thymus vulgaris L.)

Abstract: Determinação de óleos essenciais de alfavaca (Ocimum gratissimumLDepartamento de Química, Caixa Postal 3037, 4 Universidade Estadual do Ceará, Curso de Ciências Biológicas, RESUMO: O presente trabalho teve como objetivo a caracterização de plantas frescas e secas (comerciais) de alfavaca, orégano e tomilho, a obtenção dos óleos essenciais através do método de arraste a vapor e a quantificação dos compostos químicos por CG/EM. As plantas frescas e as secas comerciais foram submetidas às análises de umidade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
1
7
1
4
Order By: Relevance
“…The initial moisture content of the O. gratissimum leaves used in the drying processes varied between 79.13 and 82.13%. Previous research of the same species reported initial moisture content values of 76.50% (Luz et al, 2009) and 78.26% (Borges et al, 2012), which are close to those determined in the present study.…”
Section: Resultssupporting
confidence: 91%
“…The initial moisture content of the O. gratissimum leaves used in the drying processes varied between 79.13 and 82.13%. Previous research of the same species reported initial moisture content values of 76.50% (Luz et al, 2009) and 78.26% (Borges et al, 2012), which are close to those determined in the present study.…”
Section: Resultssupporting
confidence: 91%
“…We used clinical isolates E.coli 27 and S. aureus 358, multidrug resistant bacterial strains, provided by Institute Oswaldo Cruz. Bothstrains were maintained in Brain Heart Infusion (BHI), and for testing for resistancemodifying activity, the strains were suspended in a test tubewith distilled water to obtain a suspension with turbidity equivalent to 0.5 on the Mc Farland scale (1 x 10 8 CFU /mL).…”
Section: Microorganismsmentioning
confidence: 99%
“…25 However, the chemical composition of the oil varies according to the genotype of the plant, geographical origin, environmental conditions, season of the year, method of extraction of this oil and its preservation. 26 Several chemical shave been found in the essential oil of O. gratissimum (OEOg), such as Eugenol and Thymol, 27 γ-muurolene and β-caryophyllene, 28 α-bisabolene and γ-terpinene, 29 1.8-cineole and β-selinene, 30 and Geraniol and p-cymene. 31 OEOg is grouped into some chemo types according to the major constituents found, such as Eugenol, Thymol and Geraniol.…”
Section: Introductionmentioning
confidence: 99%
“…Aguiar et al (2015) obtained 0.45% EO yield, when the plants were cultivated in the Crato region of Ceará, Brazil. Borges et al (2012) compared the EO yield from fresh and dry leaves of clove basil plants. The fresh leaves yielded 0.13% EO content, similar to this study.…”
Section: Characteristics Of Growth Field and Clove Basil Essential Oilmentioning
confidence: 99%